Efektivitas Model Pembelajaran Blended Learning dalam Meningkatkan Kemandirian dan Hasil Belajar Peserta Didik pada Masa Pandemi Covid-19 - Mufidah, Nur Lailatul; Surjanti, Jun (Ekuitas: Jurnal Pendidikan Ekonomi, 2021)
This research aims to analyze the effectiveness of the Blended Learning learning model that was applied during the Covid-19 pandemic and is seen based on the responses of students. In addition, this research also aims to analyze how effectively the Blended Learning model is able to increase learning independence and student learning outcomes. This research belongs to the type of quantitative research that uses a quasi-experimental approach with a Posttest Only Control Group Design. The population in this study was class XI IPS at SMAN 1 Puri, Mojokerto. The sampling technique used was the Simple Random Side technique and obtained class XI IPS 1 as the control class and XI IPS 3 as the Experiment class. The research data comes from primary and secondary data. Primary data comes from posttest scores, independence questionnaires and student responses. Meanwhile, secondary data was obtained based on documentation on the value and attendance of students. This research succeeded in proving that blended learning learning could be carried out with a percentage of 95.83%. The effectiveness of the Blended learning model shows a percentage of 73.84%. The implementation of the Blended Learning model is also effective in increasing learning independence which is shown in the Sign value (2-tailed) is 0.021 <0.05, and can also improve student learning outcomes shown in the Sign (2-tailed) value is 0.032 <0, 05.